1972
DOI: 10.1159/000464486
|View full text |Cite
|
Sign up to set email alerts
|

The Gerbich Blood Group System, Especially in Melanesians

Abstract: Investigations of the Gerbich blood group system in Melanesians of Papua/ New Guinea are described. Over 50% of members of certain population groups are Gerbich negative, and anti-Gea (‘naturally-occurring’) is present in about 10% of Ge (a-) people. The distribution of populations with high Ge (a-) incidence is not explicable at present. A Gerbich antibody (anti-Ge 1) with a new specificity has been investigated, and the following phenotypes are now distinguishable: Ge 1, 2, 3 (some Melanesians and almost all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A good example is Papua New Guinea where in some coastal parts of the country, up to 20% of the population may be Gerbich blood group negative (6) and the commonest IgG antibody detected is an Anti‐Gea. The second example of a Scianna null blood type (Sc:‐1,‐2) with Anti Sc3 present was also detected in this country and a study has shown the presence of numerous donors of this extremely rare type (7). Unfortunately, access to these donors is now not easy because of the difficult economic and social situation of this country.…”
Section: Really Rare Donorsmentioning
confidence: 60%
“…A good example is Papua New Guinea where in some coastal parts of the country, up to 20% of the population may be Gerbich blood group negative (6) and the commonest IgG antibody detected is an Anti‐Gea. The second example of a Scianna null blood type (Sc:‐1,‐2) with Anti Sc3 present was also detected in this country and a study has shown the presence of numerous donors of this extremely rare type (7). Unfortunately, access to these donors is now not easy because of the difficult economic and social situation of this country.…”
Section: Really Rare Donorsmentioning
confidence: 60%
“…The frequency of Jk(a−b−) is 0·9%‐1·4% in Pacific Island populations but <0·1% in Caucasians . Furthermore, 10%‐50% of Melanesian populations are Ge− (Gerbich phenotype) .…”
Section: Rare Blood Types With Higher Frequencies In the Asia Pacificmentioning
confidence: 99%
“…Two individuals,(P. L. and K. W.) with elliptocytic red cells, who apparently lack sialoglycoproteins /3, P/ and y, have recently been described (Anstee et al, 1984). The red cells of P. L. and K. W. lack the Gerbich blood-group antigen (Ge), absence of which is extremely rare except in certain areas of Papua-New Guinea (Race & Sanger, 1975;Booth & McLoughlin, 1972). Consequently, erythrocyte membranes from other Genegative individuals were tested to determine whether changes similar to those found in P. L. and K. W. were also present.…”
mentioning
confidence: 99%